Immediate transfusion in African children with uncomplicated severe anemia - Maitland, K; Kiguli, S; Olupot-Olupot, P; Walker, S (Massachusetts Medical Society, 2019)
BACKGROUND The World Health Organization recommends not performing transfusions in African children hospitalized for uncomplicated severe anemia (hemoglobin level of 4 to 6 g per deciliter and no signs of clinical severity). However, high mortality and readmission rates suggest that less restrictive transfusion strategies might improve outcomes. METHODS In this factorial, open-label, randomized, controlled trial, we assigned Ugandan and Malawian children 2 months to 12 years of age with uncomplicated severe anemia to immediate transfusion with 20 ml or 30 ml of whole-blood equivalent per kilogram of body weight, as determined in a second simultaneous randomization, or no immediate transfusion (control group), in which transfusion with 20 ml of whole-blood equivalent per kilogram was triggered by new signs of clinical severity or a drop in hemoglobin to below 4 g per deciliter. The primary outcome was 28-day mortality. Three other randomizations investigated transfusion volume, postdischarge supplementation with micronutrients, and postdischarge prophylaxis with trimethoprim–sulfamethoxazole. RESULTS A total of 1565 children (median age, 26 months) underwent randomization, with 778 assigned to the immediate-transfusion group and 787 to the control group; 984 children (62.9%) had malaria. The children were followed for 180 days, and 71 (4.5%) were lost to follow-up. During the primary hospitalization, transfusion was performed in all the children in the immediate-transfusion group and in 386 (49.0%) in the control group (median time to transfusion, 1.3 hours vs. 24.9 hours after randomization). The mean (±SD) total blood volume transfused per child was 314±228 ml in the immediate-transfusion group and 142±224 ml in the control group. Death had occurred by 28 days in 7 children (0.9%) in the immediate-transfusion group and in 13 (1.7%) in the control group (hazard ratio, 0.54; 95% confidence interval [CI], 0.22 to 1.36; P=0.19) and by 180 days in 35 (4.5%) and 47 (6.0%), respectively (hazard ratio, 0.75; 95% CI, 0.48 to 1.15), without evidence of interaction with other randomizations (P>0.20) or evidence of between-group differences in readmissions, serious adverse events, or hemoglobin recovery at 180 days. The mean length of hospital stay was 0.9 days longer in the control group. CONCLUSIONS There was no evidence of differences in clinical outcomes over 6 months between the children who received immediate transfusion and those who did not. The triggered-transfusion strategy in the control group resulted in lower blood use; however, the length of hospital stay was longer, and this strategy required clinical and hemoglobin monitoring.